2015
DOI: 10.1016/j.rpor.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

SBRT and extreme hypofractionation: A new era in prostate cancer treatments?

Abstract: Background: Considering that PC could have a low ␣/␤ ratio, similar to late-reacting normal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
0
10
0
5
Order By: Relevance
“…In fact, several studies have reported the efficacy of moderate hypofractionated RT for patients with prostate cancer [42][43][44][45]. Moreover, the clinical outcomes of extreme hypofractionated RT for those with prostate cancer have been recently reported [46][47][48]. According to these features of prostate cancer and because of the biological and physical advantages in CIRT, it is considered that CIRT is appropriate for the management of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have reported the efficacy of moderate hypofractionated RT for patients with prostate cancer [42][43][44][45]. Moreover, the clinical outcomes of extreme hypofractionated RT for those with prostate cancer have been recently reported [46][47][48]. According to these features of prostate cancer and because of the biological and physical advantages in CIRT, it is considered that CIRT is appropriate for the management of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have reported the e cacy of moderate hypofractionated RT for patients with prostate cancer [42][43][44][45]. Moreover, the clinical outcomes of extreme hypofractionated RT for those with prostate cancer have been recently reported [46][47][48]. According to these features of prostate cancer and because of the biological and physical advantages in CIRT, it is considered that CIRT is appropriate for the management of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It uses nonuniform radiation beams to achieve tightly conformal dose distributions and ultra-high doses of over 80 Gy can be safely delivered [4,5]. This is especially relevant in light of the combination of IGRT and IMRT/ volumetric modulated arc radiotherapy in the context of stereotactic body radiation therapy/ stereotactic ablative radiotherapy (SBRT/SABR) treatments allowing delivery of higher total biological equivalent doses and/or higher dose per fraction [6]. However, in order for IMRT to be effective in reducing toxicity while increasing the target dosedespecially in regard to the adjacent membranous urethra, which remains at risk for urethral strictures with dose escalationdit is essential to localise the prostate or target volume accurately.…”
Section: Intensity-modulated Radiotherapymentioning
confidence: 99%
“…SIMAT was developed in order to improve dose conformity to the target volume and allow for dose escalation to the target volume [20]. There have been a substantial number of reports confirming that dose escalation results in improvement in biochemical relapse rates [6,7]. The delivery of SIMAT, as with any dose conforming method of treatment to the prostate, requires precise localisation of the prostate apex.…”
Section: Appendixmentioning
confidence: 99%